A reactive polyurethane hot melt adhesive with long open time and broad substrate adaptability and a preparation method thereof
Patent Information
- Application Number
- CN202611348897.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]但是平贴工艺中板材贴合面积大,需要胶粘剂具有长开放时间,来保证足够长的操作时间,还会面对不同的基材和膜材,而现有技术中的反应型聚氨酯热熔胶大多开放时间太短,针对不同的基材和膜材还需要“专胶专用”,导致反应型聚氨酯热熔胶在平贴工艺中适用性较差
兼具长开放时间和广谱基材适应性的反应型聚氨酯热熔胶通过添加A组分、B组分和C组分,形成协同作用,使所得热熔胶同时具有以下特点:
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of polyurethane, and more specifically, to a reactive polyurethane hot melt adhesive with both long open time and broad substrate adaptability, and a method for preparing the same. Background Technology
[0002] Composite panels are a relatively new material in the home decoration industry in recent years, and they are very popular due to their ease of use and durability. They are generally made of PVC sheets / MDF / VPS laminated with high-polymer PVC / PET film, aluminum foil, melamine paper, or leather, etc. They are lightweight, fire-resistant, mildew-resistant, and insect-resistant, easy to install, have a good decorative effect, and are convenient to maintain. In the decoration field, their main applications are ceilings, baseboards, partitions, and furniture / kitchenware, and they are now expanding into areas such as floor tiles and exterior wall panels.
[0003] Composite panels, as decorative materials, require waterproofing, moisture resistance, aesthetics, and versatility. Flat-mounted composite panels are primarily used in home / kitchenware and interior decoration materials, widely applied in interior partitions, ceilings, wall cladding, home / kitchenware panels, and various decorative panels in various buildings such as residences, office buildings, shops, hotels, and industrial plants. Among these, home / kitchenware panels and wall panels have experienced rapid growth in recent years. Since 2019, new substrate materials for flat-mounted panels have emerged, including magnesium oxide boards, ceramic tiles, and aluminum panels, while surface materials have begun to include PET film, wood veneer, non-woven fabric, and melamine paper to meet diverse application needs.
[0004] In recent years, due to changing consumer attitudes, rapid advancements in materials, and the ease and convenience of assembly, the application of wall panels has entered a period of rapid growth, leading many profile cladding companies to vigorously develop flat-laying services. However, the solvent-based adhesives commonly used in flat-laying continuously release organic solvents after bonding, resulting in strong odors and high VOC emissions. This causes significant unpleasant smells in the wall panels, harming not only the environment but also the health of those exposed to the area. Furthermore, the continuously released organic solvents can corrode the adhesive materials over time, leading to poor adhesion, blistering, and affecting the aesthetic appearance.
[0005] Reactive polyurethane hot melt adhesives possess the rapid positioning and curing properties of hot melt adhesives, significantly improving production efficiency in industrial production. Furthermore, their moisture-crosslinking and curing characteristics give them high bonding strength to wood, metals, plastics, and glass, along with excellent heat resistance, durability, chemical resistance, and water resistance. Therefore, reactive polyurethane hot melt adhesives are widely used across various industries and are the preferred alternative to solvent-based adhesives, improving production efficiency, enhancing the environment, and protecting human health.
[0006] However, the large bonding area of the boards in the flat lamination process requires the adhesive to have a long open time to ensure a sufficiently long working time. It also faces different substrates and film materials. Most of the reactive polyurethane hot melt adhesives in the existing technology have too short an open time, and "special adhesives for different substrates and film materials" are required, resulting in poor applicability of reactive polyurethane hot melt adhesives in the flat lamination process. Summary of the Invention
[0007] In order to extend the open time of reactive polyurethane hot melt adhesive while improving its adaptability to different substrates and film materials to meet its requirements in the flat lamination process, this application provides a reactive polyurethane hot melt adhesive with both long open time and broad substrate adaptability, and its preparation method.
[0008] In a first aspect, this application provides a reactive polyurethane hot melt adhesive that combines long open time with broad substrate adaptability, employing the following technical solution: A reactive polyurethane hot melt adhesive with both long open time and broad substrate adaptability comprises the following raw materials in parts by weight: Component A: 60-100 parts; Component A is a long main chain and long side chain bio-based polyester polyol. Component B is 55-85 parts, and component B is a crystalline polyester polyol; Component C is 10-20 parts, and component C is silane-modified amine-terminated polyurethane prepolymer; 170 parts of auxiliary components, including polyether polyol, polyester polyol, hydroxy acrylic polyol and resin; 50 parts isocyanate; Antioxidant 0.4 parts.
[0009] By adopting the above technical solution, component A possesses high wettability and wide adaptability, enabling the product to form good adhesion to various substrates; component B has low crystallinity, allowing the product to maintain good flexibility at low temperatures without becoming brittle, while also providing high final bond strength after complete curing; component C has good toughness and a fast curing speed, giving the product a certain degree of shrinkage resistance in the initial stage. Components A, B, and C work synergistically, resulting in a hot melt adhesive with the following characteristics: long open time; wide substrate adaptability, with good adhesion to substrates and films such as PVC film, PET film, aluminum plates, and wood-plastic composites; good flexibility at low temperatures, without becoming brittle or shrinking. Therefore, this achieves the effect of extending the open time of reactive polyurethane hot melt adhesive while improving its adaptability to different substrates and films, thus meeting the requirements of its application in flat lamination processes.
[0010] Optionally, the raw materials of component A include sebacic acid, 1,5-pentanediol and polymer polyol. The molecular weight of component A is 2000-3500 g / mol, the functionality is 2, it is liquid at room temperature, and the proportion of long side chain flexible units is 20-40%.
[0011] Optionally, component A is prepared by polycondensation of the raw materials.
[0012] Optionally, the raw materials for component B include adipic acid, 1,4-butanediol, 1,6-hexanediol, and a catalyst. The molecular weight of component B is 2000-3500 g / mol, the functionality is 2, and the melting point is 45-75℃.
[0013] Optionally, the B component is prepared by polycondensation of the raw materials.
[0014] Optionally, the raw materials for component C include polytetrahydrofuran ether diol, isocyanate, silane coupling agent, and catalyst.
[0015] Optionally, the C component is prepared by polymerizing the raw materials.
[0016] Optionally, the isocyanate is MDI-100.
[0017] Optionally, the antioxidant is antioxidant 1010.
[0018] Secondly, this application provides a method for preparing a reactive polyurethane hot melt adhesive that has both long open time and broad substrate adaptability, using the following technical solution: A method for preparing a reactive polyurethane hot melt adhesive with both long open time and broad substrate adaptability includes the following steps: Component A, Component B, auxiliary components, and antioxidants are added to a reaction vessel and heated to 130–150°C to completely melt the raw materials. The mixture is then stirred until homogeneous. The mixture is kept under vacuum for 2–3 hours, maintaining a vacuum level below -0.096 MPa. Nitrogen gas is used to vent the mixture, and the temperature is lowered to below 120°C. Isocyanate and Component C are then added and stirred until homogeneous. The mixture is then kept under vacuum at 115–125°C, maintaining a vacuum level below -0.096 MPa. After the reaction is complete, nitrogen gas is used to vent the mixture, and the material is discharged to obtain a reactive polyurethane hot melt adhesive that has both a long open time and broad substrate compatibility.
[0019] By adopting the above technical solution, the reactive polyurethane hot melt adhesive can improve its adaptability to different substrates and films while increasing its open time, so as to meet its needs in the flat lamination process.
[0020] In summary, this application has the following beneficial effects: Reactive polyurethane hot melt adhesives that combine long open time and broad substrate adaptability achieve synergistic effects by adding components A, B, and C, resulting in hot melt adhesives with the following characteristics: It has wide substrate adaptability, with good adhesion to PVC film, PET film, aluminum plate and wood-plastic composite substrates; low viscosity and good fluidity; good thermal stability, with viscosity change not exceeding 100% in 2 hours under open conditions at 120℃; long open time, not less than 10 minutes under environmental conditions of 23℃ and 50% RH; high initial tack and good positioning effect; good toughness after curing, good flexibility at low temperature, no brittleness, no shrinkage, and no risk of bulging at high temperature; convenient construction, no VOC release, environmentally friendly and harmless. Detailed Implementation
[0021] The present application will be further described in detail below with reference to the embodiments. It should be noted that: unless otherwise specified, the conditions in the following embodiments shall be performed under conventional conditions or conditions recommended by the manufacturer, and the raw materials used in the following embodiments shall be commercially available unless otherwise specified. Preparation Example
[0022] Preparation Example 1 Component A is a self-synthesized long-chain, long-side-chain bio-based polyester polyol, comprising the following raw materials: Sebacic acid, 202g, purchased from Shanghai Yuhao Fine Chemical Co., Ltd., CAS No. 111-20-6; 1,5-pentanediol, 104g, purchased from Shandong Yinuo Biomass Materials Co., Ltd., CAS No. 111-29-5; Polymer polyol, specifically castor oil modified aliphatic ether polyol, 131g, purchased from Guangzhou Haoyi New Material Technology Co., Ltd.
[0023] The preparation method of component A is as follows: In the pre-esterification stage, all the sebacic acid, 1,5-pentanediol, and 20% of the total weight of polymer polyol are added. Under nitrogen protection, the mixture is stirred at 140°C for 2 hours to complete the pre-esterification and remove some water. After the pre-esterification is completed, the remaining 80% of the weight of polymer polyol is added, the temperature is raised to 180°C, and the reaction is carried out for 3 hours. During the process, the acid value is measured and controlled within the range of 50-80 mgKOH / g to ensure that the functionality of the product meets the requirements. The main chain esterification and side chain grafting are completed. After the reaction is completed, the vacuum is drawn to below -500 Pa, the temperature is raised to 200°C, and the reaction is continued for 4 hours. The molecular weight is measured and stopped when the expected value is reached. Finally, the product is cooled to 80°C, and the vacuum is broken with nitrogen to obtain component A.
[0024] The molecular weight requirement for component A is 2000–3500 g / mol, with long-chain flexible units accounting for 20–40%. In this preparation example, component A has a molecular weight of 2000 g / mol, a functionality of 2, is liquid at room temperature, and has long-chain flexible units accounting for 30%.
[0025] Preparation Example 2 Component B is a self-synthesized crystalline polyester polyol, comprising the following raw materials: Adipic acid 146g, purchased from Shenma Industry Co., Ltd., CAS No. 124-04-9; 1,4-butanediol 45g, purchased from Sichuan Tianhua Chemical Group Co., Ltd., CAS No. 110-63-4; 1,6-hexanediol 59g, purchased from Lishui Nanming Chemical Co., Ltd., CAS No. 629-11-8; catalyst, tetrabutyl titanate 200ppm, purchased from Anhui Taichang Chemical Co., Ltd., CAS No. 5593-70-4.
[0026] The preparation method of component B is as follows: Add all raw materials to the reaction vessel, stir evenly under nitrogen protection, heat to 210℃, and keep the reaction at this temperature until the acid value is <1.0mgKOH / g. After the esterification reaction is completed, dehydrate and de-alcoholize under reduced pressure at 210℃ and -0.09MPa. Control the reaction time, take samples to test the hydroxyl value and adjust the molecular weight. Stop the reaction when the expected value is reached (hydroxyl value range 32~56mgKOH / g, corresponding to a molecular weight of 2000~3500); the product is component B.
[0027] The molecular weight of component B should be 2000–3500 g / mol, with a functionality of 2 and a melting point of 45–75 °C. In this preparation example, the molecular weight of component B is 3500 g / mol, with a functionality of 2 and a melting point of 65 °C.
[0028] Preparation Example 3 Component C is a self-synthesized silane-modified amine-terminated polyurethane prepolymer, comprising the following raw materials: 200g of polytetrahydrofuran ether diol was purchased from BASF, Germany (CAS No. 24979-97-3); 35g of isocyanate, specifically HDI, was purchased from Bayer, Germany (CAS No. 3779-63-3); 18g of silane coupling agent, specifically 3-aminopropyltrimethoxysilane, was purchased from Momentive, USA (CAS No. 13822-56-5); and 200ppm of catalyst, specifically dibutyltin dilaurate, was purchased from Air Products, USA (CAS No. 77-58-7).
[0029] The preparation method of component C is as follows: Polytetrahydrofuran ether diol is dehydrated under vacuum at 120℃ for 2 hours, cooled to 40℃, isocyanate and catalyst are added, and the mixture is stirred and heated to 60℃ under nitrogen protection for 3 hours. The -NCO content of the product is detected and found to be within the expected range (3-4%). Then, silane coupling agent is added dropwise to seal the product, and the reaction is carried out at 65℃. The -NCO content is detected by sampling until there is no -NCO and the -NCO has completely reacted. Vacuum degassing is performed for 15 minutes, and then nitrogen is used to break the vacuum to obtain component C.
[0030] Preparation Example 4 Auxiliary components include the following raw materials: 50g of polyether polyol; 60g of polyester polyol; 40g of hydroxyacrylic acid polyol; 20g of resin.
[0031] The polyether polyol was purchased from Shandong Lanxing Dongda, CAS number 25322-69-4. The polyester polyol was purchased from Asahi Kasei Corporation, Japan, CAS number 132459-81-5. The hydroxyl acrylic polyol was purchased from SK Chemicals, South Korea. The resin was purchased from Liaoyang Liaohua Qida Chemical, CAS number 9010-79-1.
[0032] The auxiliary component is prepared as follows: Weigh polyether polyol, polyester polyol, hydroxyacrylic acid polyol and resin into a reaction vessel, heat to 140°C, and wait for the solid materials to completely melt. After stirring evenly, control the temperature at 140°C and dehydrate under vacuum for 120 minutes, keeping the vacuum degree at -0.1 MPa. After dehydration is completed, vent with nitrogen to obtain the auxiliary component. Example Example 1
[0033] A reactive polyurethane hot melt adhesive with both long open time and broad substrate adaptability comprises the following raw materials in appropriate amounts: Component A 60g, prepared from Preparation Example 1; Component B 85g, prepared from Preparation Example 2; Component C 20g, prepared from Preparation Example 3; Auxiliary component 170g, prepared from Preparation Example 4; Isocyanate, MDI-100, 50g; Antioxidant, Antioxidant 1010, 0.4g.
[0034] Antioxidant: Purchased from Yixing Angel Synthetic Chemical Co., Ltd., CAS No. 6683-19-8.
[0035] Isocyanate: Purchased from Yantai Wanhua Polyurethane Co., Ltd., CAS No. 101-68-8.
[0036] A method for preparing a reactive polyurethane hot melt adhesive with both long open time and broad substrate adaptability includes the following steps: weighing component A, component B, auxiliary components, and antioxidant and adding them to a reaction vessel, heating to 140°C, and after the solid materials are completely melted and stirred evenly, controlling the temperature at 140°C, maintaining the temperature and applying vacuum for 120 minutes, with the vacuum degree maintained at -0.1 MPa; cooling to 110°C, venting with nitrogen, adding MDI-100 and component C, stirring until uniform, maintaining the temperature at 120°C and applying vacuum for 180 minutes, with the vacuum degree maintained at -0.1 MPa; after the reaction is completed, venting with nitrogen and discharging the material to obtain the reactive polyurethane hot melt adhesive with both long open time and broad substrate adaptability. Example 2
[0037] The difference between this embodiment and Embodiment 1 is that the amounts of each raw material are different: Component A 80g, prepared from Preparation Example 1; Component B 70g, prepared from Preparation Example 2; Component C 15g, prepared from Preparation Example 3; Auxiliary component 170g, prepared from Preparation Example 4; Isocyanate, MDI-100, 50g; Antioxidant, Antioxidant 1010, 0.4g. Example 3
[0038] The difference between this embodiment and Embodiment 1 is that the amounts of each raw material are different: Component A 100g, prepared from Preparation Example 1; Component B 55g, prepared from Preparation Example 2; Component C 10g, prepared from Preparation Example 3; Auxiliary component 170g, prepared from Preparation Example 4; Isocyanate, MDI-100, 50g; Antioxidant, Antioxidant 1010, 0.4g. Comparative Example
[0039] Comparative Example 1 The difference between this comparative example and Example 2 is that component C is not included in the raw materials, and the amounts of each raw material are as follows: Component A 70g, prepared from Preparation Example 1; Component B 80g, prepared from Preparation Example 2; Auxiliary component 180g, prepared from Preparation Example 4; Isocyanate, MDI-100, 56g; Antioxidant, Antioxidant 1010, 0.4g.
[0040] Comparative Example 2 The difference between this comparative example and Example 2 is that component A is not included in the raw materials, and the amounts of each raw material are as follows: Component B 70g, prepared from Preparation Example 2; Component C 15g, prepared from Preparation Example 3; Auxiliary component 250g, prepared from Preparation Example 4; Isocyanate, MDI-100, 54g; Antioxidant, Antioxidant 1010, 0.4g.
[0041] Comparative Example 3 The difference between this embodiment and Embodiment 2 is that component B is not included in the raw materials, and the amounts of each raw material are as follows: Component A 70g, prepared from Preparation Example 1; Component C 15g, prepared from Preparation Example 3; Auxiliary component 250g, prepared from Preparation Example 4; Isocyanate, MDI-100, 57g; Antioxidant, Antioxidant 1010, 0.4g.
[0042] Comparative Example 4 The difference between this embodiment and Embodiment 2 is that component A and component C are not included in the raw materials, and the amounts of each raw material are as follows: Component B 100g, prepared from Preparation Example 2; auxiliary component 230g, prepared from Preparation Example 4; isocyanate, MDI-100, 52g; antioxidant, antioxidant 1010, 0.4g.
[0043] Comparative Example 5 The difference between this embodiment and Embodiment 2 is that components A, B, and C are absent from the raw materials; instead, Dynacoll 7360 polyester polyol from Evonik Industries, Germany, is used instead. The amounts of each raw material are as follows: 100g of Dynacoll 7360 polyester polyol from Evonik, Germany; 230g of auxiliary components, which were prepared in Preparation Example 4; 52g of isocyanate, MDI-100; and 0.4g of antioxidant, antioxidant 1010.
[0044] Performance testing.
[0045] Detection methods.
[0046] The hot melt adhesives prepared in the above embodiments and comparative examples were subjected to the following tests, and the test results are detailed in Table 1.
[0047] Complete curing conditions: stand for 7 days at 23±2℃ & 50±5%RH.
[0048] Viscosity: Refer to standard "GB / T 2794-2022"; the test method is cone-plate method: use cone-plate viscometer to automatically collect steady-state viscosity value; the sample size is 1ml; the test conditions are temperature 120℃±0.5℃, rotor No.4, speed 40RPM, and measurement after constant temperature equilibrium for 1min; the measured index is apparent viscosity, unit mPa·s.
[0049] Opening time: Refer to standard "HG / T 3716-2003"; the test method is manual: coating → placement → pressing → peeling; the sample specification is a wet film thickness of 30μm; the test conditions are room temperature 23.0℃±1.0℃ and relative humidity 50%±5%; the measured index is the maximum allowable time for the bonded material to peel off and fail under the specified bonding conditions.
[0050] Viscosity growth rate: Refer to standard "GB / T 13353-2022"; the test method is to seal the sample and place it in an oven at 120℃±2℃ and heat it. Take samples at 1 hour intervals to test the viscosity; the sample specification is 50ml / vial; the test conditions are temperature 120℃±0.5℃, rotor No. 4, speed 40R, and measurement after constant temperature equilibrium for 1 minute; the measured index is the viscosity growth after high temperature treatment compared with the initial state.
[0051] Solid content: Refer to standard "GB / T 2793-2022"; the test method is oven drying method: the adhesive sample is evenly coated on a pre-weighed aluminum foil tray, placed in an oven at 105℃±2℃ for 2 hours, cooled and weighed, and the solid content is calculated; the sample size is 1.5±0.1g wet sample; the test conditions are 105.0℃±2.0℃, normal pressure, dried for 2 hours, cooled to room temperature (23℃) and weighed; the measured index is the solid content percentage, and 100% in the table indicates that the system is a 100% solid content reactive adhesive with no volatile components.
[0052] Compatibility: Refer to standard "HG / T 4366-2012"; the test method is visual inspection: melt the adhesive solution and observe whether it separates, precipitates, becomes cloudy or settles, and evaluate visually; the sample size is 10ml; the test conditions are room temperature environment and visual observation; the measured index is the degree of compatibility and miscibility.
[0053] Curing speed: Refer to standard "HG / T 4363-2012"; The test method is to apply adhesive to aluminum sheets, stack them and apply pressure, and peel them off every 30 seconds to observe whether the adhesive surfaces can be separated. The time when they cannot be separated is the initial curing time; The sample specifications are adhesive layer thickness ≈ 0.2 mm, overlap area 25 mm × 25 mm; The test conditions are 23℃ ± 1℃, 50%RH ± 5%, standard pressure 0.1 MPa; The measured index is the speed of cross-linking and curing at room temperature.
[0054] Shrinkage at 5℃: Refer to standard "GB / T 13465.5-2009"; the test method is to inject the adhesive into a special U-shaped mold (inner cavity 50mm×10mm×2mm), cure at 23℃ for 24h, demold, trim both ends to be flat, measure the initial length with a digital caliper at 23.0℃±0.5℃, and then place the sample in an environmental chamber at (5.0℃±0.5℃) for 4h and measure the length again. The difference before and after is the shrinkage amount; the sample specification is single molding, measured after demolding; the test conditions are 5.0℃±0.3℃, unrestrained free shrinkage; the measured index is the average shrinkage amount at one end, the smaller the value, the better the effect.
[0055] Brittleness at 5℃: Refer to standard "GB / T 5470-2008"; the test method is to pre-cool the cured adhesive strip (25mm×6mm×2mm) in an environmental chamber at (5.0℃±0.5℃) for 1 hour, then quickly bend it by both ends and observe whether it breaks, pulverizes, or makes an obvious brittle sound; the sample specifications are adhesive strip size 25×6×2mm³; the test conditions are 5.0℃±0.5℃, pre-cooling for 1 hour, and manual bending; the measured index is the degree of low-temperature brittleness.
[0056] 40℃ bulging phenomenon: Refer to standard "HG / T 4654-2014"; the test method is to place the bonded aluminum-PVC composite board in a 40℃ constant temperature chamber for 7 days, and visually inspect whether bubbles, bulging or delamination appear at the interface of the adhesive layer; the sample size is an aluminum plate / PVC film composite sample (100×100mm); the test conditions are 40.0℃±1.0℃, 7 days, no external force; the measured index is the degree of expansion and bulging of the adhesive layer.
[0057] Aluminum plate bonded to PVC film: Refer to standard "GB / T 7124-2022"; the test method is to prepare aluminum plate-PVC film overlap shear test specimens, cure at 23℃ for 72 h and then test the tensile shear strength and observe the failure mode; the specimen specifications are overlap length 12.5 mm, width 25 mm, adhesive layer thickness 0.2 mm; the test conditions are 23℃±1℃, 72 h, loading rate 50 mm / min; the measured indicators are interface bonding effect and material failure degree.
[0058] Wood-plastic composite (WPC) bonded to PVC film: Refer to standard "GB / T 7124-2022"; The test method is to prepare a shear test specimen of the WPC-PVC film overlap, cure it at 23℃ for 72 h, test the tensile shear strength, and observe the failure mode; The specimen specifications are an overlap length of 12.5 mm, a width of 25 mm, and an adhesive layer thickness of 0.2 mm; The test conditions are 23℃±1℃, 72 h, and a loading rate of 50 mm / min; The measured indicators are the interface bonding effect and the degree of material failure.
[0059] Table 1 Test Results
[0060] Comparing the bonding results of Examples 1, 2, and 3, it was found that Example 1 performed worse than Example 2 at low temperatures, exhibiting uneven force after curing and being more prone to brittleness at low temperatures; Example 3 had low initial bond strength and was more prone to shrinkage after curing. Within this range, the product can ensure bonding performance to various types of substrates, but the suitable operating temperature range will change with variations in the proportion of different raw materials; Example 2 exhibits the most balanced performance and the widest suitable operating temperature range.
[0061] A comparison of the test results of Comparative Examples 1, 2, 3, 4, and 5 with those of Example 2 in the table reveals that Component A significantly improves the adhesive performance of the product, resulting in better adhesion, wider adaptability, and a certain degree of adhesion even to some difficult-to-bond substrates. Component B effectively mitigates low-temperature brittleness, maintaining good adhesion at low temperatures compared to Evonik's Dynacoll 7360 polyester polyol, without exhibiting brittleness. Furthermore, the addition of Component C optimizes the product's shrinkage performance, enhances the colloid's toughness, prevents shrinkage during low-temperature bonding, and also improves curing speed and adhesion.
[0062] The test results of the above embodiments show that the reactive polyurethane hot melt adhesive of this application has a long open time, which is convenient for construction; it has 100% solid content, no VOC release, and is environmentally friendly and harmless; it is suitable for use with low adhesive amount, which helps to reduce costs; it has good adhesion to a variety of substrates and high bonding strength; and at a high temperature of 40°C, there is no bulging on the bonding surface, and at a low temperature of 5°C, there is no shrinkage at the bonding edge, and the adhesive layer does not become brittle or detach.
[0063] Based on the above performance comparison, the product obtained by the technical solution of this application has superior overall performance, longer open time, higher construction efficiency, better thermal stability, is environmentally friendly and harmless, has a high cost performance, and its excellent strength and adaptability meet the bonding requirements of various materials. It also has a certain adhesion to substrates with low surface energy and has a certain bonding effect in a wide temperature range. It has broad application prospects and unique competitive advantages.
[0064] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A reactive polyurethane hot melt adhesive with both long open time and broad substrate adaptability, characterized in that, Including the following parts by weight of raw materials: Component A: 60-100 parts; Component A is a long main chain and long side chain bio-based polyester polyol. Component B is 55-85 parts, and component B is a crystalline polyester polyol; Component C is 10-20 parts, and component C is silane-modified amine-terminated polyurethane prepolymer; 170 parts of auxiliary components, including polyether polyol, polyester polyol, hydroxy acrylic polyol and resin; 50 parts isocyanate; Antioxidant 0.4 parts.
2. The reactive polyurethane hot melt adhesive according to claim 1, characterized in that: The raw materials of component A include sebacic acid, 1,5-pentanediol and polymer polyol. The molecular weight of component A is 2000-3500 g / mol, the functionality is 2, it is liquid at room temperature, and the proportion of long side chain flexible units is 20-40%.
3. The reactive polyurethane hot melt adhesive according to claim 2, characterized in that: The A component is prepared by polycondensation of the raw materials.
4. The reactive polyurethane hot melt adhesive according to claim 1, characterized in that: The raw materials for component B include adipic acid, 1,4-butanediol, 1,6-hexanediol, and a catalyst. The molecular weight of component B is 2000-3500 g / mol, the functionality is 2, and the melting point is 45-75℃.
5. The reactive polyurethane hot melt adhesive according to claim 4, characterized in that: The B component is prepared by polycondensation of the raw materials.
6. The reactive polyurethane hot melt adhesive according to claim 1, characterized in that: The raw materials for component C include polytetrahydrofuran ether diol, isocyanate, silane coupling agent, and catalyst.
7. A reactive polyurethane hot melt adhesive with both long open time and broad substrate adaptability according to claim 6, characterized in that: The C component is prepared by polymerizing the raw materials.
8. The reactive polyurethane hot melt adhesive according to claim 1, characterized in that: The isocyanate is MDI-100.
9. A reactive polyurethane hot melt adhesive with both long open time and broad substrate adaptability according to claim 1, characterized in that: The antioxidant is antioxidant 1010.
10. A method for preparing a reactive polyurethane hot melt adhesive with both long open time and broad substrate adaptability as described in any one of claims 1 to 9, characterized in that, Includes the following steps: Component A, Component B, auxiliary components, and antioxidants are added to a reaction vessel and heated to 130–150°C to completely melt the raw materials. The mixture is then stirred until homogeneous. The mixture is kept under vacuum for 2–3 hours, maintaining a vacuum level below -0.096 MPa. Nitrogen gas is used to vent the mixture, and the temperature is lowered to below 120°C. Isocyanate and Component C are then added and stirred until homogeneous. The mixture is then kept under vacuum at 115–125°C, maintaining a vacuum level below -0.096 MPa. After the reaction is complete, nitrogen gas is used to vent the mixture, and the material is discharged to obtain a reactive polyurethane hot melt adhesive that has both a long open time and broad substrate compatibility.
